Kebijakan Pemerintah Daerah Kabupaten Brebes Dalam Pemberdayaan Petani Bawang Merah - Dra. Sulistiowati, M.Si, Candra Apriyanto Dra. Rr. Hermini S, M.Si (Journal of Politic and Government Studies, 2013)
AbstractRed Onion is one commodity in the District of Bradford and is the largest production center in Indonesia. With onion potential is so great, is actually the ideal conditions for a positive impact on the realization of the welfare of the farmers in the district of Bradford, but seems still far from expectations when in reality there are many farmers who live in poverty. Therefore, the government must be able to function well where the local government authority to make policy areas to provide increased participation, and community empowerment initiatives aimed at improving the welfare of the people. The policies taken by the government in terms of local empowerment, especially for onion farmers in the Brebes Distric, is expected to solve problems that can increase farmers' welfare.Keywords: Policies, Empowerment, Farmer, Red Onions